Analisis Hukum Dalam Kasus Serangan Siber Pada Bank Syariah Indonesia (BSI) - Zulfikar, Faiz Raudhin; Merah Harley, Airiique Bintang (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The case of the breach of Bank Syariah Indonesia (BSI) by the LockBit 3.0 hacker group that occurred on May 8, 2023 became one of the largest cybersecurity incidents in Indonesia. With the theft of personal data of more than 15 million customers, this incident had a significant impact on public trust and data security in the banking sector. This research uses a normative juridical method to analyze how regulations related to cyber attacks that occur against banks are regulated which include rights, obligations of both institutions and customers as well as administrative and criminal sanctions that can be given to protect customer interests. The results showed that the regulation related to cyber attacks in Indonesia has been regulated in the Law and the cause of the hacking case that occurred was because Bank Syariah Indonesia (BSI) did not pay sufficient attention to the digital security system used.